Implementation of Good University Governance Principles in Procurement of Human Resources in Universitas Brawijaya - Ika Wuriyanti; Hamidah Nayati Utami; I Gede Eko Putra Sri Sentanu (Sekolah Pascasarjana Universitas Brawijaya, 2020)
This research is motivated by the importance of the procurement of Human Resources at Universitas Brawijaya. The principles of Good University Governance (GUG) become a value and the best choice for universities as a basis for intense competition to become a leading tertiary institution in Indonesia and oriented to world-class universities. This research is designed to examine the implementation of the principles of good university governance (GUG) consisting of transparency, accountability, responsibility, fairness, and independence at every stage of human resource procurement (from recruitment to reward and punishment) in Universitas Brawijaya. This research is qualitative research with a grounded theory research approach. In this approach, researchers are responsible for developing other theories that arise from observing a group. This research uses data collection techniques with interviews, observation and documentation study, interviews conducted require three informants from the Civil Service Section. The results of this study indicate the procurement of Human Resources in UB has used the principles of GUG, transparency, accountability, responsibility, fairness, and independence in the recruitment process of educators and education staff, selection of educators and education staff, placement in assignments and positions that are accordingly, training and development, preparation of career paths, up to discipline enforcement and awarding.